2000
DOI: 10.1007/s003300050979
|View full text |Cite
|
Sign up to set email alerts
|

Rectal tumour staging: MR imaging using pelvic phased-array and endorectal coils vs endoscopic ultrasonography

Abstract: The aim of this study was to compare MR imaging and endoscopic ultrasonography (EUS) for the local staging of rectal tumours. Forty-nine patients were examined on a 1.5-T MR unit using either a pelvic phased-array coil (n = 37) alone or combined with an endorectal coil (n = 12). Sagittal and axial sequences with T2-weighted fast spin-echo and axial T1-weighted spin-echo techniques were employed. The EUS technique was performed using a flexible endosonoscope. The results were compared with findings at histopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
70
1
9

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(86 citation statements)
references
References 30 publications
6
70
1
9
Order By: Relevance
“…When directly compared to ERUS for a T3 tumor, Blomqvist et al [30] had 11 false positives with ERUS compared to 8 for MRI. On the other hand, Akasu et al [31] in their series found that, two third of staging errors in invasion depth resulted from overstaging and were most common with pT2 tumors.…”
Section: C B Amentioning
confidence: 99%
“…When directly compared to ERUS for a T3 tumor, Blomqvist et al [30] had 11 false positives with ERUS compared to 8 for MRI. On the other hand, Akasu et al [31] in their series found that, two third of staging errors in invasion depth resulted from overstaging and were most common with pT2 tumors.…”
Section: C B Amentioning
confidence: 99%
“…MR imaging also consistently allows accurate measurement of the depth of extramural tumor spread, determination of mesorectal involvement, and prediction of CRM involvement (Fig 12). With use of external coils (eg, phased-array surface coils), the overall accuracy of MR imaging for the T staging of rectal cancer varies from 65% to 86% (8,26,(43)(44)(45)(46), with considerable interobserver variability. In recent studies, the reported accuracy has varied from 86% to 100% (8,35,45,46).…”
Section: Clinical Impact Of Mr Imagingmentioning
confidence: 99%
“…• Мультидисциплинарное лечение рака эндометрия у которых риск развития местного рецидива наиболее высок [17]. Наибольший интерес представляет группа па-циентов, у которых по данным различных обследований, выполненных после завершения химиолучевой терапии, удалось достичь полного клинического регресса [18].…”
unclassified